2012
DOI: 10.1007/s00424-012-1147-2
|View full text |Cite
|
Sign up to set email alerts
|

Properties of blebbistatin for cardiac optical mapping and other imaging applications

Abstract: Blebbistatin is a recently discovered myosin II inhibitor. It is rapidly becoming a compound of choice to reduce motion artifacts during cardiac optical mapping, as well as to study cell motility and cell invasion. Although blebbistatin has a number of advantages over other electromechanical uncouplers, many of its properties have yet to be addressed. Here we describe several methodological issues associated with the use of blebbistatin, including its spectral properties, reversibility, and its effect on tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 34 publications
3
62
0
Order By: Relevance
“…Nevertheless, the energetic demand of the uncoupled heart is predictably less than that of a contracting heart, and it is possible that the decrease in flow is not sufficient to promote ischaemia. In support of this, Swift et al (2012) have demonstrated that NADH accumulation in ischaemic tissue is five times slower in the presence of blebbistatin than that seen in control conditions. It cannot be ruled out that vasoconstriction is a reflection of a reduction in energetic demand.…”
Section: Methodological Considerationsmentioning
confidence: 60%
See 2 more Smart Citations
“…Nevertheless, the energetic demand of the uncoupled heart is predictably less than that of a contracting heart, and it is possible that the decrease in flow is not sufficient to promote ischaemia. In support of this, Swift et al (2012) have demonstrated that NADH accumulation in ischaemic tissue is five times slower in the presence of blebbistatin than that seen in control conditions. It cannot be ruled out that vasoconstriction is a reflection of a reduction in energetic demand.…”
Section: Methodological Considerationsmentioning
confidence: 60%
“…Exp Physiol 98.5 (2013) pp 1009-1027 the mitochondria and cytosol, reducing ATP availability despite inhibition of contractile activity and a reduction in net oxygen consumption (de Tombe et al 1992;Stapleton et al 1998). Swift et al (2012) have previously reported that blebbistatin can form a precipitate when mixed in solutions at room temperature and can accumulate within the coronary vasculature. This is unlikely to be a factor in the present experiments, because all solutions were heated to 37 • C and passed through a 5 μm micropore filter before perfusion.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy cannot be applied in vivo because of the toxicity of the commonly used dyes and the incompatibility of the in vivo use of electromechanical uncouplers as well as their effects on AP morphology. 6,[44][45][46][47] Here, we provide first experimental evidence that a GEVI, expressed stably and homogeneously in cardiac myocyte membranes in vivo, can overcome these limitations. We first scrutinized the VSFP-imaging modality in Langendorff-perfused hearts and validated its use for the visualization of myocardial electric conduction under physiological and pathological heart rate and rhythm ( Figure 5).…”
Section: Discussionmentioning
confidence: 93%
“…Stock solutions of 10 mM (-)-blebbistatin (Sigma-Aldrich, St. Louis, MO) and 5 mM RH 237 (Molecular Probes, Eugene, OR) dissolved in 100% DMSO were kept at Ϫ20°C and were used at 15 M (0.15% DMSO) and 8 M (0.16% DMSO) final concentrations, respectively. Warming of blebbistatin before dilution increased the consistency of inhibition of cardiac contraction (31). Fresh aliquots of Rhod-2 AM (Molecular Probes) gave the largest transient sizes with the lowest background levels.…”
Section: Methodsmentioning
confidence: 99%